APOBEC3C‐Mediated NF‐κB Activation Promotes Malignant Progression of Gliomas - Chao Zhang; Tao Yang; Yuhang Tang; Dong Yu; Shiqiang Hou; Ning Lin; Qun Li (Immunity, Inflammation and Disease)
ABSTRACT Objective To analyze the clinicopathological features, immunological characteristics, and prognostic value of APOBEC3C in gliomas, and to verify the specific mechanism by which it mediates the malignant progression of gliomas. Methods mRNA‐seq data from 693 glioma patients in the CGGA database and 697 glioma patients in the TCGA were analyzed, respectively. In addition, single‐cell sequencing data were obtained from the CGGA database. Bioinformatics methods were applied to reveal the possible mechanisms of APOBEC3C‐mediated malignant progression of gliomas. Moreover, western blot, transwell, and cell‐scratch assays were used to explore the potential mechanisms of APOBEC3C‐mediated glioma invasion and migration. Results APOBEC3C was enriched in malignant glioma subtypes and was a potential biomarker for mesenchymal subtypes in glioma patients. It was closely associated with glioma inflammation and immunity. Additionally, APOBEC3C is a potential independent prognostic factor for glioma, and inhibition of APOBEC3C expression can suppress the EMT process in glioma cells through the NF‐κB signaling pathway. Conclusion APOBEC3C is a potential biomarker for glioma patients. It is closely related to the clinicopathology of glioma and may be a potential immunotherapy target for glioma patients.